Determination of the heavy metal contents and the benefit/cost analysis of Hypericum salsugineum in the vicinity of Salt Lake - Demir, Aynur; Furtana, Gökçen Baysal; Tekşen, Mehtap; Tipirdamaz, Rukiye (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this study, Hypericum salsugineum, an endemic halophytic plant growing around Salt Lake, was analyzed to determine the heavy metals (chromium, lead, copper, zinc and nickel) on it and on the soil it grew. The phytoremediation potential of H. salsugineum was evaluated. In addition, the benefit cost (B/C) analysis was performed for its potential use in phytoremediation. The plant and soil samples were collected from Eskil and Cihanbeyli between May and September in 2016. A total of 300 soil and plant samples were analysed for heavy metal content. Statistical and standard benefit/cost analyses were performed for assessment. The capacity of accumulating the aforementioned heavy metals was found to be high in H. salsugineum. It was found that Ni and Pb ratio exceeded optimum values in its habitat, and H. salsugineum accumulated available Ni and Pb. When the plant was evaluated in terms of benefit/cost, B/C ratio was greater than 1 during the useful life of the study. This conclusion increases the ecological and economical values of H. Salsugineum, effecting its potential use in phytoremediation.